Isospora lunaris n. sp. (Apicomplexa: Eimeriidae) from the domestic Java sparrow in Japan. Issue 2 (April 2017) - Tokiwa, Toshihiro; Kojima, Atsushi; Sasaki, Shun; Kubota, Rie; Ike, Kazunori
Abstract: Five individuals of the domestic Java sparrows, Lonchura oryzivora (Aves: Estrildidae), were examined for coccidian parasites. Sporulated oocysts had two sporocysts containing four sporozoites each. Sporulated oocysts (n = 30) were spherical, with a two splinter-like polar granules. Oocyst size was 22.1 × 20.7 (20.0–25.0 × 20.0–22.5) μm. They had a thick wall that consisted of a pale yellow outer layer and a dark yellow inner layer, and lacked micropyle and residuum. Sporocysts (n = 60) were elongated ovoid 14.1 × 9.8 (12.5–15.0 × 7.5–10.0) μm, smooth walled, and colorless, with crescent-shaped Stieda and indistinct substieda bodies. Sporocyst residuum was interspersed between sporozoites. Sporozoites were oriented transverse to the sporocyst longitudinal axis. On the basis of morphological data, the species isolated in the present study is a new species of Isospora and propose the name Isospora lunaris n. sp. Graphical abstract: